Optimal control of the UPFC for the stability of electrical networks - Ababsia, Houria; Dib, Djalel; Djeddi, Abdelghani (International Journal of Applied Power Engineering (IJAPE), 2025)
The unified power flow controller (UPFC) is a crucial element in contemporary power systems, specifically engineered to augment the manageability and adaptability of power transmission in electrical networks. UPFC provides instantaneous modifications to voltage magnitude, phase angle, and line impedance by using sophisticated power electronics and control algorithms. This research examines the function of the unified power flow controller (UPFC) in enhancing the power quality of electrical networks. The UPFC's capacity to dynamically regulate and optimize power flow assists in minimizing voltage fluctuations, decreasing transmission line losses, and improving system stability. In addition, UPFC effectively addresses problems such as voltage sags, swells, and flickers, hence enhancing the resilience and dependability of the power supply. This research highlights the importance of unified power flow control (UPFC) technology in improving system performance and power quality of electrical networks via a thorough examination of its applications. This article presents research on the performance of the unified power flow controller (UPFC) device in a network, specifically focusing on the use of PID and FO-PID controllers for regulating active and passive power.